Analisis Clustering Global Living Cost Berdasarkan Socioeconomic Status Menggunakan Algoritma DBSCAN - Perdana Putra, Siswadi; Aryo Anggoro, Dimas (Universitas Budi Darma, 2024)
The development of the world economy is currently undergoing a very complex phase characterised by very different changes. These changes have a significant impact on the cost of living and quality of life of people in various countries around the world. Factors such as government policies, economy, income, transport, fuel play an important role in various changes in the world economy. Then this research aims to cluster the cost of living on the